Предмет: Алгебра,
автор: Женькаааа
решите уравнение: а) (x-2)(x+3)=x(2-x) б) х(2х+1)=(2х+1)2
Ответы
Автор ответа:
0
а) (x-2)(x+3)=x(2-x)
X(2)+3x-2x-6=2x-X(2) ---- число "2" после икс пиши сверху
2X(2)+x-2x=6
2X(2)-x=6
x(2x-1)=6
x=6 или 2x-1=6
2x=7
x=3,5
ответ: 6; 3,5
б) х(2х+1)=(2х+1)(2)
2х(2)+х=4х(2)+1+4х
2х(2)+х-4х(2)-4х=1
-2х(2)-3х=1
х(-2х-3)=1
х=1 или -2х-3=1
-2х=4
х=-2
ответ: 1;-2
Похожие вопросы
Предмет: Информатика,
автор: qaqa10
Предмет: География,
автор: birukova152
Предмет: Русский язык,
автор: burulmirkalimova2
Предмет: Литература,
автор: kka2001
Предмет: Алгебра,
автор: tufetulova